2005
DOI: 10.1113/jphysiol.2004.080218
|View full text |Cite
|
Sign up to set email alerts
|

The role of the third extracellular loop of the Na+,K+‐ATPase α subunit in a luminal gating mechanism

Abstract: Na + ,K + -ATPase is responsible for maintaining the cross-membrane Na + and K + gradients of animal cells. This P-type ATPase works via a complex transport cycle, during which it binds and occludes three intracellular Na + ions and then two extracellular K + ions, which it then releases on the other side of the membrane. The cation pathway through the protein, and the structures responsible for occluding cations inside the protein, have not yet been definitely identified. We used cysteine mutagenesis to explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
11
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 35 publications
6
11
0
Order By: Relevance
“…And mutating that Thr to Cys renders the Na͞K pump susceptible to inhibition by omeprazole (31), while making it less sensitive to inhibition by ouabain (31,36). This correlation, together with similarities between omeprazole inhibition of H͞K pumps and cardiotonic steroid inhibition of Na͞K pumps, supports the idea that cardiotonic steroids dock in the space above TM6 shown in Fig.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…And mutating that Thr to Cys renders the Na͞K pump susceptible to inhibition by omeprazole (31), while making it less sensitive to inhibition by ouabain (31,36). This correlation, together with similarities between omeprazole inhibition of H͞K pumps and cardiotonic steroid inhibition of Na͞K pumps, supports the idea that cardiotonic steroids dock in the space above TM6 shown in Fig.…”
Section: Discussionsupporting
confidence: 64%
“…The residue equivalent to P789 is a Thr in all Na,K-ATPase ␣ subunits, in which it has been suggested to play a role in regulating access of external cations to their binding sites (31). In other work (32), we have found that this Thr marks a point of narrowing of the ion pathway of PTX-bound Na͞K pumpchannels, reinforcing structural similarity between the Na,KATPase ␣ subunit and Ca-ATPase in this region.…”
Section: Discussionmentioning
confidence: 72%
“…4) is surrounded by transmembrane helices 5-8. This location indicates a cation permeation pathway which agrees with the proposed Na + release order [20] as well as mutagenesis studies that implicate nearby amino acid residues in Na + conduction [21] and K + affinity [22]. A second putative pathway agrees more with a location near transmembrane helices 3-5, which is supported by mutagenesis studies reporting a change in the apparent affinity for K + [23].…”
Section: Electrostatics Of Ion Permeation Pathwayssupporting
confidence: 69%
“…Our finding that the N-terminus of M5 sticks out of the detergent micelle suggests that the remainder of the peptide is embedded in the hydrophobic interior. Burial of the C-terminal end in the micelle agrees with the disposition of native M5, where labelling with sulfhydryl reagents from the aqueous phase is possible for residues Gly803-Val805 in mutated M5 [57], but not for Pro801 and Leu802.…”
Section: Discussionsupporting
confidence: 58%